Determinants of Quality of Life in Myasthenia Gravis Patients - Szczudlik, Piotr; Sobieszczuk, Ewa; Szyluk, Beata; Lipowska, Marta; Kubiszewska, Justyna; Kostera-Pruszczyk, Anna (Frontiers in Neurology, 2020)
Background: Although approximately half of myasthenia gravis (MG) patents achieve remission, for the remaining group MG is often a life-long disease. Better understanding of the determinants of Quality of Life (QoL) in MG is needed to optimize treatment goals in chronic cases. Material and Methods: We performed a single center cross-sectional study in 339 MG adult patients (64.9 % women), with ocular or generalized disease. SF-36 and a structured questionnaire was administered, including information on previous and current MG severity, medications, comorbidities, education, occupation and BMI of the patient. Mean disease duration was 7.5 + 9.3 years. Current age was 51.6 + 18.3 years, 55% had Early-Onset (<50 years) MG. Results: There were no statistically significant differences in mean SF-36 subscores between women and men. Worse MGFA class was related to lower QoL in physical (PCS) and mental (MCS) subscore (p=0.000 for both). Patients with MGFA I-II class had significantly better QoL in physical and mental subscores than patients with more severe MG (p<0.005). Late-onset MG patients had worse QoL than EOMG in physical score domain PCS (p=0.049). Overweight and obese patients had lower PCS (p=0.002) and MCS (p=0.038) than patients with normal BMI. University education was related to statistically higher PCS (p=0.015) and MCS (p=0.006). QoL in currently employed was better in PCS and MCS (p=0.000), with white collar workers reporting higher PCS (p=0.049) than the remaining group. Patients living with family evaluated their MCS (p=0.015) better than living alone. Moderate physical activity (twice a week) improved PCS (p=0.045). Conclusion: Our study confirmed that greater severity of symptoms, age, age of onset but also BMI, type of work, education status and physical activity affect QoL in MG.